“Make A-meme-rica great again!”: studying the memers among Trump supporters in the 2020 US presidential election on Twitter via hashtags #maga and #trump2020 - Tran, Huu Dat (Kansas State University, 2021)
The study, consisting of three parts and based on the theoretical framework of social network analysis, political spamming, and framing theory, analysed a corpus of 220,336 tweets from 96,820 unique users posted on Twitter between October 27 and November 2, 2020. It investigates the participation of social media, particularly Twitter, and internet memes in political discourse, positioning such concepts in the political context of the 2020 US presidential election. The study attempts to better understand Donald Trump, his community of supporters, and their political discourse and activities during the 2020 US presidential election; thus, an investigation into their Twitter social network should prove fruitful. By probing into the community of supporters of the incumbent Donald Trump, specifically the group of internet memers (an internet slang describing people who create or distribute memes), on Twitter during the 2020 US presidential election, the study reveals the most active and influential users within the network, the likelihood of those users being spamming bots, and their tweets’ content. Such analysis is relevant in understanding Twitter users related to the hashtags, their affiliations, and the nature of such accounts. Systematic, objective, and quantitative content analysis of internet memes found in the corpus should determine (1) the memes’ target, (2) how were the targets portrayed in the memes, and (3) the main themes, or ideas, of the internet memes posted within the community of Donald Trump supporters. Finally, findings shall be discussed, from which assessment, prediction, and serviceable data are provided in the hope that the study can contribute to building a solid foundation for future research concerning internet memes, social media, and political communication.
Keywords: Twitter; Social media; Political communication; Donald Trump; Social networkMemes